Valorization of alkaloid containing wastewater: Bioconversion of lupanine into added-value products by newly isolated microorganisms - Vasquez Christodoulou, Marlen (My University, 2026)
Parmaki S, Vyrides I, Vasquez MI, Hadjiadamou I, Barbeitos CBM, Ferreira FC, Afonso CAM, Drouza C, Koutinas M, Valorization of alkaloid containing wastewater: Bioconversion of lupanine into added-value products by newly isolated microorganisms, 6th International Conference on Sustainable Solid Waste Management, Naxos, Greece, 13-15 June 2018.